Correlations between physical activity and quality of life in entrepreneurs from Wrocław, Poland - Daniel Puciato; Dawid Bączkowicz; Michał Rozpara (BMC, 2023)
Abstract Background Limited physical activity is one of the main reasons for the rapid increase in the prevalence of diseases of affluence, which can lead to premature deaths in adults. Quality of life may be one of potential determinants of physical activity. The aim of this article is to identify the relationships between physical activity and quality of life in entrepreneurs from Wroclaw, Poland. Methods A cross-sectional study was conducted on a group of 616 entrepreneurs (216 women and 400 men). A diagnostic survey method was used with a direct interview technique. The research tools included the International Physical Activity Questionnaire Short Form and the World Health Organization Quality of Life Questionnaire. Results Among the studied entrepreneurs, along with their higher ratings of overall quality of life, the odds of high rather than low levels of physical activity increased nearly fivefold (OR 4.86, CI 3.34-7.07). Entrepreneurs with higher assessment levels of their perceived health condition were nearly twice as likely to report high rather than low physical activity levels (OR 1.92, CI 1.42-2.59). The conditional probability of high rather than low levels of physical activity also increased in the entrepreneurs with higher assessments of quality of life in the physical, psychological, social, and environmental domains, by 34%, 11%, 5%, and 6%, respectively. Conclusion Programs promoting physical activity among entrepreneurs, which focus on moderate and high intensity exercise, should be considered desirable in the context of the study findings. Activities aimed at improving quality of life in the physical and psychological domains as a potential determinant of the level of physical activity of entrepreneurs are also worth recommending.